Kyrgyz Republic : Developing Agri-Food Value Chains - World Bank (World Bank, Washington, DC, 2018)
The prevalence of small farmers and small-scale agri-food processors creates unique challenges for agri-food value-chain development in Kyrgyzstan. That is, the Kyrgyz farm structure itself, with its dominance of small farmers, is one of the main constraints for the effective functioning of modern value chains, preventing them from delivering high incomes and improved livelihoods for smallholders. But this structure also provides one of the main opportunities for developing the value chain. Small-scale agri-food processors are rarely successful in establishing sustainable partnerships with small farmers unless there are strong market signals that facilitate these partnerships. Such strong market signals for Kyrgyz agri-food producers/processors are found in niche and premium markets of products that require specialized and labor-intensive agricultural production. Therefore, when market failures are addressed by public policy interventions, small farmers and small-scale agri-food processors have improved access to markets, more opportunities to capture value, and more opportunities to improve their livelihoods.